Analyse énonciative de have to et comparaison avec le modal must - Pauline Serpault (Anglophonia)
This article explores various uses of have to in contemporary English, relying on empirical data. The analysis is carried out within the framework of the theory of predicative and enunciative operations as set out by Antoine Culioli, and aims to identify a set of functional invariants holding across a wide range of contextual meanings. Our formal representations partially build on the operations marked by the verb have (localisation, a specific operation of location), and the infinitive particle to (“visée” understood as the construction of a notional occurrence or as the distinction of one value in a notional domain), as we suggest that the functioning of have to can be perceived as a product of their combination. These representations also attempt to pinpoint the difference between have to and must, while accounting for the cases in which their meanings seem to overlap.